Thermodynamics of a bouncer model: A simplified one-dimensional gas - Leonel, Edson D. [UNESP]; Livorati, Andre L. P. (Elsevier B.V., 2015)
Some dynamical properties of non interacting particles in a bouncer model are described. They move under gravity experiencing collisions with a moving platform. The evolution to steady state is described in two cases for dissipative dynamics with inelastic collisions: (i) for large initial energy; (ii) for low initial energy. For (i) we prove an exponential decay while for (ii) a power law marked by a changeover to the steady state is observed. A relation for collisions and time is obtained and allows us to write relevant observables as temperature and entropy as function of either number of collisions and time. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Bouncer model; Diffusion in energy; Scaling